Subject and authorship of records related to the Organization for Tropical Studies (OTS) in BINABITROP, a comprehensive database about Costa Rican biology - Julián Monge-Nájera; Vanessa Nielsen-Muñoz; Ana Beatriz Azofeifa-Mora (Revista de Biología Tropical, 2013)
BINABITROP is a bibliographical database of more than 38 000 records about the ecosystems and organisms of Costa Rica. In contrast with commercial databases, such as Web of Knowledge and Scopus, which exclude most of the scientific journals published in tropical countries, BINABITROP is a comprehensive record of knowledge on the tropical ecosystems and organisms of Costa Rica. We analyzed its contents in three sites (La Selva, Palo Verde and Las Cruces) and recorded scientific field, taxonomic group and authorship. We found that most records dealt with ecology and systematics, and that most authors published only one article in the study period (1963-2011). Most research was published in four journals: Biotropica, Revista de Biología Tropical/ International Journal of Tropical Biology and Conservation, Zootaxa and Brenesia. This may be the first study of a such a comprehensive database for any case of tropical biology literature. BINABITROP es una base de datos bibliográfica con más de 38 000 registros sobre los ecosistemas y organismos de Costa Rica. En contraste con bases de datos comerciales como Web of Knowledge y Scopus, que excluyen a la mayoría de las revistas científicas publicadas en los países tropicales, BINABITROP registra casi por completo la literatura biológica sobre Costa Rica. Analizamos los registros de La Selva, Palo Verde y Las Cruces. Hallamos que la mayoría de los registros corresponden a estudios sobre ecología y sistemática; que la mayoría de los autores sólo registraron un artículo en el período de estudio (1963-2011) y que la mayoría de la investigación formalmente publicada apareció en cuatro revistas: Biotropica, Revista de Biología Tropical/International Journal of Tropical Biology, Zootaxa y Brenesia. Este parece ser el primer estudio de una base de datos integral sobre literatura de biología tropical.